Proses Penggarapan Karya Tari Sang Pratijna - Mariska, Revi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to describe the process of creating the dance work “Sang Pratijna” inspired by the Timbang Kepala Kebo tradition in Pangkalan Balai, South Sumatra. The problem focuses on the stages of the process of creating the Sang Pratijna dance, which include the stages of exploration, improvisation, formation and evaluation. The research method used is qualitative descriptive. Data were collected through direct observation of the practice process, interviews with choreographers and dancers. Data were analyzed in depth to understand the stages of the dance creation process, starting from the exploration of ideas to the evaluation of the dance work as a whole. This study concludes that the process of creating the “Sang Pratijna” dance emphasizes the combination of spiritual commitment and the role of women in preserving local culture through symbolic movements.